Do we need to know more about the effects of hormones on lower urinary tract dysfunction? ICI‐RS 2014. Issue 2 (February 2016) - Hanna‐Mitchell, Ann T.; Robinson, Dudley; Cardozo, Linda; Everaert, Karel; Petkov, Georgi V.
Abstract : This review article reflects the presentations and subsequent discussions during a think tank at the 5th International Consultation on Incontinence Research Society's annual meeting, held in Bristol, UK (September 22–24, 2014). It reviews the current state of knowledge on the role of hormones in lower urinary tract dysfunction (LUTD) and overactive bladder (OAB) and in particular: highlights some specific basic research findings from discussion participants; reviews future research topics; and discusses potential new therapeutic opportunities for LUTD and OAB. The role of the large conductance voltage‐ and Ca 2+ ‐activated K + (BK) channels, as novel therapeutic targets for OAB was discussed, in particular as recent studies on human detrusor smooth muscle suggest that estradiol exerts a direct non‐genomic activation of the BK channels. Recent developments on the roles of sex hormones on diuresis, as well as the roles of melatonin and vitamin D on LUTD were also discussed. It was concluded that further basic science and translational studies are needed to better understand hormonal regulatory mechanisms of the lower urinary tract and the implications for novel treatment options for LUTD and OAB. Neurourol. Urodynam. 35:299–303, 2016 . © 2016 Wiley Periodicals, Inc.